2017
DOI: 10.1177/1470320317705232
|View full text |Cite
|
Sign up to set email alerts
|

Molecular remodeling of the renin-angiotensin system after kidney transplantation

Abstract: Objective:We aimed at assessing the molecular adaptation of the renin-angiotensin system (RAS) after successful kidney transplantation (KTX).Materials and methods:In this prospective, exploratory study we analyzed 12 hemodialysis (HD) patients, who received a KTX and had excellent graft function six to 12 months thereafter. The concentrations of plasma Angiotensin (Ang) peptides (Ang I, Ang II, Ang-(1–7), Ang-(1–5), Ang-(2–8), Ang-(3–8)) were simultaneously quantified with a novel mass spectrometry-based metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The total variation (V) of each corresponding line scan was calculated according to the following formula: Briefly, angiotensin peptide levels and aldosterone were measured in conditioned lithium-heparin plasma at 37°C. Stable isotope-labeled internal standards for each metabolite were added to stabilized plasma samples at a concentration of 200 pg/mL and subjected to LC-MS/ MS-based angiotensin quantification by Attoquant Diagnostics, as previously described (3,7,16).…”
Section: Methodsmentioning
confidence: 99%
“…The total variation (V) of each corresponding line scan was calculated according to the following formula: Briefly, angiotensin peptide levels and aldosterone were measured in conditioned lithium-heparin plasma at 37°C. Stable isotope-labeled internal standards for each metabolite were added to stabilized plasma samples at a concentration of 200 pg/mL and subjected to LC-MS/ MS-based angiotensin quantification by Attoquant Diagnostics, as previously described (3,7,16).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, angiotensin peptide levels were measured following 30 min of equilibration in conditioned lithium-heparin plasma at 37 °C and subsequent stabilization of equilibrium peptide levels. Stable isotope-labeled internal standards for each angiotensin metabolite (Ang I, Ang II, Ang-(1–7), Ang-(1–5), Ang-(2–8), Ang-(3–8)) as well as the deuterated internal standard for aldosterone (aldosterone D4) were added to stabilized plasma samples at a concentration of 200 pg/ml and subjected to liquid chromatography tandem-mass spectrometry (LC-MS/MS)-based angiotensin and steroid quantification by Attoquant Diagnostics as described previously 50 . As previously reported, using protease inhibitor-stabilized and equilibrated samples for angiotensin peptide quantification resulted in similar qualitative outcomes 51 .…”
Section: Methodsmentioning
confidence: 99%
“…While the RAS after KTx is constantly affected by various hemodynamic and immunological factors, we have previously shown that the systemic RAS is restored early to physiological levels, i.e. within the first months after KTx indicating that it could present a potential target for pharmacological intervention 29 . However, during the past decade, the focus of interest on the RAS has shifted to the role of the local/tissue RAS in specific tissues 3032 .…”
Section: Discussionmentioning
confidence: 98%